(untitled) (Biological Sciences - PJSIR, 2008)
Investigation of spring and well waters of the Peshawar Intermontane basin and its surroundings in the Himalayan belt of Pakistan revealed that their temperature, pH, total dissolved solids and electrical conductivity values fall within the permissible range of drinking and irrigation water except the waters in vicinity of exposed faults. Minerals in the spring water are in the order of Ca > Mg > (Na + K) with bicarbonate as the dominant anion, whereas in the well water, the order is reversed, with sulphate as the dominant anion.